Evaluation of seven commercial RT‐PCR kits for COVID‐19 testing in pooled clinical specimens. Issue 4 (17th December 2020) - Garg, Atul; Ghoshal, Ujjala; Patel, Sangram S.; Singh, D. V.; Arya, Akshay K.; Vasanth, Shruthi; Pandey, Ankita; Srivastava, Nikki
Abstract: There are more than 350 real‐time polymerase chain reaction (RT‐PCR) coronavirus disease‐2019 (COVID‐19) testing kits commercially available but these kits have not been evaluated for pooled sample testing. Thus, this study was planned to compare and evaluate seven commercially available kits for pooled samples testing. Diagnostic accuracy of (1) TRUPCR SARS‐CoV‐2 Kit (Black Bio), (2) TaqPath RT‐PCR COVID‐19 Kit (Thermo Fisher Scientific), (3) Allplex 2019‐nCOV Assay (Seegene), (4) Patho detect COVID‐19 PCR kit (My Lab), (5) LabGun COVID‐19 RT‐PCR Kit (Lab Genomics, Korea), (6) Fosun COVID‐19 RT‐PCR detection kit (Fosun Ltd.), (7) Real‐time Fluorescent RT‐PCR kit for SARS CoV‐2 (BGI) was evaluated on precharacterised 40 positive and 10 negative COVID‐19 sample pools. All seven kits detected all sample pools with low C t values (<30); while testing weak positive pooled samples with high C t value (>30); the TRUPCR Kit, TaqPath Kit, Allplex Assay, and BGI RT‐PCR kit showed 100% sensitivity, specificity, and accuracy. However, the Fosun kit, LabGun Kit, and Patho detect kit could detect only 90%, 85%, and 75% of weakly positive samples, respectively. We conclude that all seven commercially available RT‐PCR kits included in this study can be used for routine molecular diagnosis of COVID‐19. However, regarding performing pooled sample testing, it might be advisable to use those kits that performed best regarding positive identification in samples' pool, that is TRUPCR SARS‐CoV‐2 Kit, TaqPath RT‐PCR COVID‐19 Kit, Allplex 2019‐nCOV Assay, and BGI Real‐time RT‐PCR kit for detecting SARS CoV‐2.